2018
DOI: 10.1080/14767058.2018.1478958
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supine positioning on maternal hemodynamics during late pregnancy

Abstract: Women in late pregnancy experience an increase in collateral venous blood flow when lying supine, likely as a response to marked compression of the IVC in this position. However, cardiac output and aortic blood flow were found to decrease while in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
92
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 33 publications
16
92
2
4
Order By: Relevance
“…Indeed, the time spent in specific sleep states and the distribution of the sleep states across the night is known to affect blood pressure. 42 A strength of the current study is that it is the first to include an international group of women and the only one to include women from the United States; indeed, the majority of women received their care in the United States. This has particular relevance since maternal hypotension has been reported to be associated with fetal growth restriction, premature birth, and stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the time spent in specific sleep states and the distribution of the sleep states across the night is known to affect blood pressure. 42 A strength of the current study is that it is the first to include an international group of women and the only one to include women from the United States; indeed, the majority of women received their care in the United States. This has particular relevance since maternal hypotension has been reported to be associated with fetal growth restriction, premature birth, and stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we suggest that the subject lies in the left lateral position (10 • -20 • tilt), mainly to avoid caval vein compression, as even minor changes in the maternal circulation may have a detectable impact on the placental T2* value. A recent study by Humphries et al 10 found that a maternal supine position in late pregnancy reduced the flow in the inferior caval vein by 85% compared with the left lateral position. While the venous return in the azygos vein was increased, probably to compensate, cardiac output was reduced by 16%.…”
Section: How To Obtain T2*-weighted Placental Imagesmentioning
confidence: 96%
“…External factors may complicate this adaptation process. For instance, during late pregnancy, uterine weight increases and this can lead to partial/complete occlusion of the inferior vena cava and lateral displacement of the sub‐renal aorta in the supine position, affecting maternal hemodynamics and fetal oxygenation . Supine position may also result in decreased vagal activity and increased cardiac sympathetic activity when compression of the vena cava, abdominal aorta, and the iliac arteries reduces venous return and cardiac output .…”
Section: Introductionmentioning
confidence: 99%